Effects of a Cloth Panel Containing a Specific Ore Powder on Patients with Chamaecyparis obtusa (Cypress) Pollen Allergy - Suni Lee (Hindawi Limited, 2021)
Pollen allergy to Japanese cedar and cypress is a serious illness that impairs daily life and sleep, especially during pollen season. We have reported that placing a cloth panel containing a specific natural ore powder (CCSNOP) in a room may alleviate the symptoms of hay fever and may also benefit the immune system. This ore is from the Aso mountain range, a volcano on Kyushu Island in the southwestern part of Japan. The purpose of this study was to verify the effect of CCSNOP on cypress pollen. Thirty-one double-blind tests, which investigated cedar pollen allergies, were conducted from February to March 2018 and have already been reported. After this, in early April, 10 of these cases were recruited and all had CCSNOP installed in their bedrooms. Before that, various symptoms and changes in medication were recorded in a “Symptom Diary” and included a mood survey by a questionnaire, stress test using saliva amylase, changes in cypress-specific immunoglobulins IgE and IgG4 by blood sampling, and eosinophil changes. In addition, changes in 29 types of cytokines were investigated. Exposure to CCSNOP relieved symptoms and subjects decreased their intake of medication. There was no change in mood or stress, but eosinophil levels tended to decrease. Although there were no statistical changes in cypress-specific IgE or IgG4, an increase in the former and a decrease in the latter were observed in some individuals during the period of pollen dispersal. Furthermore, levels of GM-CSF and IL8 decreased significantly after use of CCSNOP. The CCSNOP was shown to be effective against cypress pollen allergy, and future investigations will be necessary to observe the long-term effects of CCSNOP.